IMPLEMENTASI MANAJEMEN KEUANGAN SEDERHANA PADA USAHA PINANG TRADISIONAL DI WAMENA: TANTANGAN DAN PELUANG DALAM KONTEKS PENDIDIKAN KEWIRAUSAHAAN - Mikaus Gombo; Ketut Suma; I Made Candiasa; I Nyoman Jampel (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyze the basic financial management practices applied by areca nut traders in Wamena, Jayawijaya Regency, Papua. The main focus is to understand how these micro-entrepreneurs manage their business finances within the local context and limited access to information. This research employs a descriptive qualitative approach, using data collection techniques such as in-depth interviews, direct field observation, and documentation of traders' business activities. The informants consist of six areca nut traders who have been running their businesses independently for at least one year. The results indicate that most traders do not yet manage their business finances systematically. Financial records of income and expenses are rarely kept, there is no clear separation between personal and business finances, and business profits are often immediately used for daily needs. Moreover, business risks such as product damage, price fluctuations, and decreased demand are not managed properly. The main factors contributing to weak financial management practices include low financial literacy, limited educational background, and lack of access to information and entrepreneurship training.This study recommends the implementation of simple, context-based entrepreneurship training programs tailored to the socio-economic background of Wamena’s community, to support the sustainability of micro-enterprises in remote areas.